Efficacy of Trichloroacetic Acid (TCA) Compared to Cryotherapy in Treating Patients with Positive VIA Result: Efikasi Trichloroacetic Acid (TCA) Dibandingkan Krioterapi sebagai Terapi Pasien dengan IVA Positif - Suwartono Herdhana; Andrijono (Indonesian Journal of Obstetrics and Gynecology, 2020)
Objective: To investigate the effectiveness TCA 85% compared to cryotherapy to treat patients with positive IVA result.Method: This is a non-inferiority randomized controlled trial study. Patients with positive VIA result referred to Jatinegara Primary Health Center were included in this study. Eligible samples were then treated with either TCA 85% or cryotherapy. The treatment was determined using a random block sampling method. Samples were then followed up 3 months after treatment in order to determine VIA result conversion.Result: Thirty-six patients were treated with TCA 85% and 36 others were treated with cryotherapy. 35 (97,2%) patients treated with TCA 85% converted to negative VIA, whereas all of the patients that were treated with cryotherapy converted to negative VIA. Bivariate analysis fisher’s exact test was then conducted with a result P-value of 1.00 (p > 0,05).Conclusion: There was no statistically significant difference of result between TCA 85% and cryotherapy for treating patients with positive VIA result.Keywords: cervical cancer, cryotherapy, TCA 85%, VIA test. Abstrak Tujuan: Mengetahui efikasi TCA 85% pada tatalaksana IVA positif dibandingkan dengan krioterapiMetode: Penelitian ini merupakan penelitian randomized control trial menggunakan metode non-inferiority study. Subyek penelitian ini merupakan pasien dengan hasil IVA positif yang dirujuk ke Puskesmas Kecamatan Jatinegara, Jakarta Timur. Tatalaksana yang diberikan ditentukan menggunakan metode random block sampling. Subyek diikuti selama 3 bulan setelah tindakan untuk menentukan hasil konversi pemeriksaan IVA.Hasil: Sbenyak 36 subjek diterapi dengan TCA 85% dan 36 lainnya diterapi dengan krioterapi. Sebanyak 35 (97,2%) pasien yang ditatalaksana dengan TCA 85% mengalami konversi menjadi IVA negatif pada follow-up bulan ke-3, sedangkan seluruh pasien yang ditatalaksana dengan krioterapi menjadi konversi menjadi IVA negatif. Dilakukan analisis bivariat fisher’s exact test dan didapatkan nilai p sebesar 1,00 (p>0,05).Kesimpulan:Tidak ada perbedaan bermakna dari efikasi penggunaan TCA 85 % dibandingkan dengan krioterapi pada terapi IVA positif.Kata kunci: kanker serviks, krioterapi, pemeriksaan IVA, TCA 85%.